Economic Impact of the 2007 Earthquake in the Water and Sanitation Sector in Four Provinces of Peru : What Did Unpreparedness Cost the Country? - Andrade, Raul (World Bank, Washington, DC, 2014)
Between 1996 and 2005, natural catastrophic events had an estimated cost of US$575.2 billion world-wide. In particular, it has been observed that developing countries are relatively more affected by such events, since its gross domestic product (GDP) have showed sharper declines than developed countries' ratios. On August 15, 2007, an earthquake measuring 7.9 on the Richter scale shook the southern part of the central coast of Peru, with devastating consequences. Given the magnitude of the damage caused, one wonders how much less the cost of rehabilitating water and sanitation systems might have been if public investment projects and management of urban utilities (companies in charge of the water and sanitation provision), had incorporated disaster risk reduction measures. For this reason, and because this is a key public sector service for the wellbeing of population, the World Bank's water and sanitation program commissioned Apoyo Consultoria S.A.C. to conduct a research on the water and sanitation sector in order to attend the following inquiry: how much unpreparedness cost to the sector providing water and sanitation services? In other words, in economic terms, what will have been the gain to society or the reconstruction savings if risk prevention measures had been included in the management of services in the sector proposed for the analysis?